Comparison Analysis Of Motorcycle Performance Between Intake Manifold Standard And Intake Manifold Racing On Yamaha Jupiter Z 2005 - IKHTIARIFQI, IKHTIARIFQI (2012)
On combustion engine, intake manifold pipe has function to distribute air-fuel mixture from carburetor to combustion chamber. Suction pipe intake manifold is not too important, but design of intake manifold can influenced on homogeneity and air-fuel mixture flow rate from carburetor to combustion engine. Objectives of this research to get and compare performance of the engine motorcycle has used intake manifold standard and intake manifold racing on Yamaha Jupiter Z 2005. Object has used is Yamaha Jupiter Z 2005 four-stroke motorcycle using carburetor Mikuni 26 mm. The testing has doing for every intake manifold to get torque, power and specific fuel consumption at 4000-9000 rpm. It use dynotest V3.3 Rextor Pro Dyno Inertia dynamometer in Mototech Laboratorium Yogyakarta. The result shows that intake manifold racing on standard piston can produce higher power and torque than intake manifold standard at low rpm and next rpm has happened changing along with the fuel consumption increased until stop the supply of air-fuel mixture because of limited supply of fuel from carburetor. In 4000 rpm, intake manifold racing on standard piston the fuel used is lower than standard intake manifold standard.